Problems in using basal body temperature recordings in an infertility clinic. Issue 6064 (26th March 1977) - Lenton, E A; Weston, G A; Cooke, I D
Abstract : Basal body temperature recordings are extensively used to diagnose and treat infertility, but too great an emphasis on the interpretation of these charts might be counter-productive in managing these patients. Several gynaecologists who use temperature charts clinically were asked to score 60 charts taken from a selection of normal and infertile women, and their results were compared with those obtained by a group of non-experts. Since the full hormonal profiles had been obtained for each of the 60 charts the accuracy of the predictions could be assessed. About 80% of the temperature charts were correctly interpreted by both groups as being either ovulatory or anovulatory but the day of ovulation was predicted correctly for only about 34% of the charts. When the charts were examined retrospectively the thermal nadir was found to coincide with the luteinising hormone surge in 43% of the charts from normal subjects but in only 25% of those from the infertile patients. Predicting the day of ovulation from the temperature recording, particularly in infertile women, is clearly unjustified.